Effects of amniotic membrane transplantation and mitomycin C on wound healing in experimental glaucoma surgery - Demir, T; Turgut, B; Akyol, N; Ozercan, I; Ulas, F; Celiker, U (Karger, 2002)
Purpose: To evaluate the effects of mitomycin C and amniotic membrane transplantation on the modulation of wound healing after glaucoma filtration surgery. Methods: Trabeculectomy was performed in 3 groups of 10 rabbit eyes each. Sponges soaked in mitomycin C were applied to the first group, and amniotic membranes were transplanted around the scleral flap in the second group; the third group was the control. The arithmetic means of fibroblast and macrophage numbers per square centimetre were calculated. Results: The mean numbers of fibroblasts and macrophages were decreased significantly in the mitomycin C group, compared with the controls (p < 0.0001). Cell counts in the amniotic membrane group were also lower than the ones in the control group for fibroblasts and macrophages (p < 0.0001, p < 0.01, respectively). The difference between the two treatment groups was statistically significant for fibroblasts (p < 0.0001), but not significant for macrophages (p > 0.05). Conclusion: In spite of the fact that amniotic membrane transplantation is less effective than mitomycin C for depressing wound healing after trabeculectomy, it might be a safer alternative in selected cases when considering severe adverse effects of antimetabolites. Copyright (C) 2002 S. Karger AG, Basel.
Keywords: trabeculectomy; wound healing; mitomycin C; amniotic membrane transplantation